Caring for those who care and promoting oral health to caregivers of patients with disabilities: a narrative review - Santos, Brenda Corrêa; Ferraz, Daniel Lobato Ferreira; Rodrigues, Camila Real Delega; Ribeiro, Marco Túlio Leandro; Bueno, Tamiris Christensen; Silva, Mirlena Mansur Dionizio da; Lopes, Márcio Ajudarte (Journal of Oral Diagnosis, 2025)
This narrative review describes the profound impact faced by caregivers of individuals with disabilities, on their physical, mental, and oral health. Caregivers, particularly women, assist with both basic and complex daily tasks, often under high levels of stress, and in many cases, face challenges related to limited personal, social, or financial support. The continuous demands lead them to neglect their own care causing consequently high rates of chronic health issues, including hypertension, mental health disorders such as depression and anxiety, and oral health problems. Research shows that these health challenges are exacerbated by limited access to healthcare services and financial constraints, with caregivers frequently isolated from social and professional support networks. To address these gaps, our review emphasizes the need for targeted interventions that provide comprehensive support for caregivers. Programs that offer emotional, logistical, and financial assistance, as well as dedicated healthcare services—including oral health—can significantly improve caregivers’ well-being. Our “Caring for those who care” initiative seeks to address these needs, and initial results underscore the importance of accessible, ongoing care for caregivers. This review advocates for systemic support structures that enhance caregivers’ quality of life, ultimately benefiting the individuals under their care.